INFLUENCE OF FERTILIZATION AND CUTTING ON FLORISTIC AND PHYTOCENOLOGICAL PROPERTIES OF FACIES (Arrenatheretum elatioris alopecurosum) - Mirko Stjepanović; Ana Skender; Gordana Bukvić; Svetislav Popović; Sonja Grljušić (Poljoprivreda, 2000)
In the period 1993-1997 investigations were conducted on natural low marshy grassland of facies Arrhenatheretum elatioris alopecurosum located 60 km west of Osijek and 7 km south of the river Drava. Variants of nitrogen fertilization, NPK fertilizers and non-fertilized were comprised in the investigation. Presence of 121 plant species of which 22 grass and grass-like species, 12 legumes and 87 other plant species was determined. On the average of five years grassland fertilization affected changes in density value of all plant groups. The highest grass density was found out with the variant fertilized with N120P12K120 and the highest legumes density appeared to be on non-fertilized variant. In 1997 Centaurea jacea, Cerastium holosteoides and Myosotis arvensis dissapeared from plant density of other species due to fertilization and mowing effect. Grasses Alopercurus pratensis and Poa pratensis var. angustifolia as well as leguminoses Trfolim pratense and Lathyrus pratensis are especially characterized by good fodder and density value.